Relationship Between Work Experience and Nurses' Ability to Perform Nursing Actions - Deharnita; Jeksi Armando; Indra Febra Mawandi (CV. Get Press Indonesia, 2024)
The healthcare sector is a dynamic and complex field, which necessitates that medical personnel, particularly nurses, possess continually evolving skills and knowledge. The objective is to examine the relationship between work experience and the competence of nurses in nursing actions, as well as other factors that may contribute to the development of such skills. The study employs a cross-sectional design, which is a research approach that collects data at a given time point with the objective of evaluating the relationship between the work experience of nurses and their ability to perform nursing actions. The majority of respondents (55.1%) have been in their current role for between one and seven years, while 39% have been in their role for between eight and 14 years, and 5% have been in their role for between 15 and 21 years. The majority of respondents (70.3%) have high work experience, while 29.7% have moderate work experience. The majority of nurses (60.2%) are considered to possess the requisite skills, while the remainder (39.8%) are deemed to have sufficient abilities. The results indicate that 60% of nurses with moderate work experience have adequate skills, while 40% have good skills. It is crucial to invest in the professional development of nurses with extensive work experience, as they tend to possess higher levels of competence. It is therefore incumbent upon health organisations to provide sustainable professional development support and opportunities to enhance the skills and competencies of their nursing staff